Physical and chemical characterization of methyl soyoil and methyl tallow esters as CI engine fuels - Yahya, Azmi; Marley, Stephen J. (1994)
Fourteen ASTM (American Society for Testing Materials) tests and four AOCS (American Oil Chemist's Society) tests were employed to characterize the fuel properties of methyl soyoil ester and methyl ta;low ester. Soybean oil and animal tallow were considered in this study as the two are leading sources for alternative CI engine fuel. Comparisons and evaluations of the properties of the esters were made against the Phillips No. 2 control diesel fuel and the ASTM D975 requirement limits set for No. 2 diesel fuel. Results from this study indicated distinct differences in the chemical compositions and some of the physical properties between the ester fuels and No. 2 diesel fuel. © 1994.